Proposed business strategy for coffee shop based on customer preferences - Tri Hendra Widadi; Dina Dellyana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Indonesia is one of the most promising markets for entrepreneurs entering the coffee shop business. The phenomenon of coffee as one of the indigenous philosophies in Indonesia inspired Kopi Nalar to have a vision of promoting the uniqueness of Indonesian coffee and providing a comfort place for the people of Jakarta. However, Kopi Nalar encountered numerous obstacles in his efforts to maintain his firm. From the middle of 2017 to the beginning of 2020, Kopi Nalar's performance was exceptional, but the impacts of COVID-19 caused significant sales drop in early 2020. Kopi Nalar has not been able to achieve the same level of sales as it did prior to the epidemic; therefore, the company must modify its business plan in response to the pandemic's effects. In this study, the selection criteria to be considered when the customer wants to go to a coffee shop are derived through interview, survey and previous research, and the importance of optional criteria is analyzed through AHP (Analytic Hierarchy Process) technique. As a result, the preference criteria of coffee shop were relatively high in order of product, place, service and marketing-promotion. From these results, business solution is formulated to implement in Kopi Nalar’s business strategies.